Cementless Total Hip Arthroplasty in Patients with Crowe Type-4 Developmental Dysplasia. Issue 5 (September 2013) - Sofu, Hakan; Şahin, Vedat; Gürsu, Sarper; Yıldırım, Timur; Issın, Ahmet; Koçkara, Nizamettin
Background: Developmental dysplasia of the hip is one of the most common causes of secondary osteoarthritis. The purpose of our study was to review clinical and radiological outcomes of reconstruction surgery using cementless total hip arthroplasty in patients with Crowe type-IV dysplastic hips. Methods: This study included eighty-seven primary total hip arthroplasties performed between January 2005 and January 2010 at our clinic in 74 patients who had Crowe type-IV developmental dysplasia of the hip. Cementless total hip arthroplasty was applied in all hips. At the clinical status analysis, any limping, the Harris hip score, surgical approach, the use of bone grafts, the presence of femoral osteotomy, any component migration, union status of the osteotomy site (if present), and any osteolysis or heterotopic ossification were noted. Mean follow-up time was 4.8 years. Results: Mean Harris hip score was improved from 41.8 points preoperatively to 86.2 points postoperatively (p<0.001). At the final clinical examination, none of the patients had severe limping. Restoration of the anatomical hip centre was achieved in all hips. Pseudoarthrosis of the femoral osteotomy site was seen in two hips (3.6%). Twelve hips (13.8%) underwent revision surgery. Neurological complications were seen in two hips (2.3%). Heterotopic ossification was detected in one hip. conclusion: Cementless total hip arthroplasty with restoration of the anatomic hip centre resulted in satisfactory clinical outcomes in patients with secondary coxarthrosis due to Crowe type IV developmental dysplasia of the hip joint.